2015
DOI: 10.1016/j.jviromet.2015.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Development of a nanoparticle-assisted PCR assay for detection of porcine epidemic diarrhea virus

Abstract: Porcine epidemic diarrhea virus (PEDV) is an important pig pathogen that can cause vomiting, diarrhea, and dehydration, leading to serious damage to the swine industry worldwide. In this study, a nanoparticle-assisted polymerase chain reaction (nanoPCR) assay targeting the N gene of PEDV was developed and the sensitivity and specificity were investigated. Under the optimized conditions for detection of PEDV RNA, the nanoPCR assay was 100-fold more sensitive than a conventional RT-PCR assay. The lower detection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…The traditional identification methods may not provide accurate distinction of the attenuated vaccine strain for the field strain. The nanoparticle-assisted RT-PCR assay has been used for rapid and accurate detection of other pig viruses [24][25][26]. The present study demonstrated that an effective nanoparticle-assisted RT-PCR assay targeting the ORF3 gene of PEDV was able to distinguish field strains from attenuated vaccine strains.…”
Section: Discussionmentioning
confidence: 65%
“…The traditional identification methods may not provide accurate distinction of the attenuated vaccine strain for the field strain. The nanoparticle-assisted RT-PCR assay has been used for rapid and accurate detection of other pig viruses [24][25][26]. The present study demonstrated that an effective nanoparticle-assisted RT-PCR assay targeting the ORF3 gene of PEDV was able to distinguish field strains from attenuated vaccine strains.…”
Section: Discussionmentioning
confidence: 65%
“…To date, several approaches have been developed for the laboratory diagnosis of PEDV, including immunohistochemistry [46], enzymelinked immunosorbent assay (ELISA) [47], RT-PCR [48], reverse transcription loop-mediated isothermal amplification (RT-LAMP) [49], a nanoparticle-assisted PCR assay [50,51], and real-time RT-PCR [35,36]. Similarly, immunohistochemical detection, PCR, and qPCR have all been developed for the detection of PCV3 [20,33,34,37].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are several ways to detect PEDV, such as molecular biological detection methods including nucleic acid probes, polymerase chain reaction (PCR), and loop-mediated isothermal amplification among others. These methods have both high precision and specificity [9][10][11][12][13][14]. However, they require precise experimental instruments and trained experimenters, and have certain restrictions on promoting grassroots production.…”
Section: Introductionmentioning
confidence: 99%